Refeeding syndrome, an undiagnosed and forgotten potentially fatal condition - Machado, Juliana Deh Carvalho [UNESP]; Suen, Vivian Marques Miguel; Chueire, Fernando Bahdur; Marchini, Julio Flávio Meirelles; Marchini, Julio Sérgio (BMJ, 2009)
Refeeding syndrome (RFS) has been well described but is also a frequently forgotten and undiagnosed complication in clinical practice, which, if untreated, may lead to death. Patients who are more prone to developing RFS are those with at least one of the following conditions: BMI <16 kg/m 2, a recent unintentional weight loss >15%, very little nutritional intake for >10 days, and/or low plasma concentrations of potassium, phosphate or magnesium before feeding; and those with at least two of the following conditions: BMI <18.5 kg/m2, a recent weight loss >10%, very little nutritional intake for >5 day, and/or a history of alcohol abuse or drug use, including insulin, chemotherapy or diuretics. We report here a patient who, after undergoing intestinal resection (short gut syndrome), presented diarrhoea, weight loss and protein-energy malnutrition. After nutritional assessment, the nutritional support team decided to feed the patient by the parenteral route. After 16 h of parenteral nutrition, the patient developed supraventricular tachycardia, hypomagnesaemia and hypocalcaemia, and RFS was diagnosed and managed. After intestinal adaptation, the patient is currently able to maintain his nutritional status with nutrition therapy by the oral route.